A bibliometric analysis: AI-driven data placement optimization in cloud replication environments - Mohd Ali, Fazlina; Mat Daud, Marizuana; Bahar, Nurhidayah; Mohd Salleh, Syahanim; Nor Rashid, Fadilla ‘Atyka; Md Yunus, Nur Arzilawati (Global Academic Excellence, 2024)
Data placement strategy using artificial intelligence (AI) in cloud replication environments has garnered significant attention in recent years. Several studies have examined this area, aiming to enhance data replication techniques by integrating AI algorithms. There is still a minimum number of studies that have discovered the trending of the existing literature that reveals cloud replication leveraging artificial intelligence techniques in the current body of knowledge. This study explores this field's significance and relevance through a bibliometric analysis, particularly its integration with artificial intelligence (AI) techniques. The study highlights key trends and developments, highlighting the collaborative potential between cloud replication and AItechnologies. The outcome of this study contributes to practitioners and researchers in evaluating and identifying potential areas for future exploration in AI-driven data placement optimization in cloud replication environments